CHALLENGE IN TEACHING ENGLISH DURING LIMITED FACE TO FACE LEARNING AT SMPN 2 TORAJA UTARA - Yizrel Nani Sallata; Judith Ratu Tandi Arrang; Arung Sudarso Tombi (Journal of Language Testing and Assessment, 2021)
The objective of the research is to find out the challenges faced by English teachers during Limited Face to Face Learning. The researcher used qualitative method in this study. The data was taken from 4 (four) English teachers which collected by using snowball sampling. To obtain data, researcher used interview and it was analyzed by using the theory of Miles and Huberman.The results of this study indicate that there are challenges in Implementation of learning with a short time allocation, The use of media in the learning process with a very short time duration, Students study inactive, Adjustment of teaching materials with the specified time, Students' understanding in receiving learning materials is still lacking due to the short allocation of time, Student Behavior Change, The application of learning is not optimal so that the material is not achieved/completed, Short time allocation in guiding students, where the character of students is different, Lack of time allocation in directing, training, and motivating students who are less disciplined ,Lack of time allocation in motivating students to extracurricular activities and other activities, The work of assignments that are not on time and the assessment of many students with a short time allocation, Limited time to evaluate students' lack of knowledge and skill.Based on the above results, the researcher concludes that teachers face several challenges in learning English after the implementation of limited face-to-face learning at SMPN 2 Toraja Utara as mentioned above.